Hypoglycaemic effect of Croton cuneatus in streptozotocin-induced diabetic rats - Torrico,Fatima (2007)
Aqueous extract of the stem barks of Croton cuneatus Klotz (Euphorbiaceae) was investigated for hypoglycaemic activity in streptozotocin(STZ)-induced diabetic rats. Increasing doses of aqueous extract (6.5, 13, 26 and 52 mg/kg i.p.) were separately administered to groups of fasted normal and diabetic rats. Plasma glucose concentration, cholesterol and changes in body weight were evaluated. The chronic intraperitoneal (i.p.) administration of the extract for 22 days was found to induce significant reduction in blood glucose level. A comparison was made between the action of the aqueous extract of C. cuneatus and the reference standard drug glibenclamide. The results of this experimental animal study indicate that this plant has an antidiabetic activity in hiperglycaemic rat models.